Atomically dispersed cerium species in NMxCe1-xO2/Al2O3 (NM = Rh, Ru) catalysts. (February 2020) - Ledwa, K.A.; Kepinski, L.; Pawlyta, M.
Graphical abstract: Highlights: HAADF-STEM revealed atomically dispersed CeOx species in NM1-x Cex O2 /γ-Al2 O3 catalysts. CeOx species may order at the surface of γ-Al2 O3 support. Concentration of CeOx species increases after reduction treatment at high temperature. Spreading of CeOx over alumina explains the amorphiztion of ceria observed by XRD. Abstract: NMx Ce1-x O2 /Al2 O3 (NM = Rh, Ru; 0 < x < 0.15) catalysts prepared by a microemulsion method contain, in addition to ceria nanoparticles, an atomically dispersed CeOx species that may be detected by high-resolution HAADF-STEM imaging. The CeOx species exist also in the samples subjected to high temperature treatment in oxidizing and reducing atmosphere, but their concentration increases rapidly after reduction above 700 °C. Generation of CeOx groups and their spreading over the alumina surface explains the effect of amorphization of ceria particles observed by XRD method.